1986
DOI: 10.1002/chin.198639018
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Oxygen Reduction on Small Supported Platinum Particles.

Abstract: Aseries of four catalysts with 5, l0, 20, and 30 wt.% Pt on carbon has been prepared and incorporated into Teflon‐bonded electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 1 publication
3
35
0
Order By: Relevance
“…Pre-treatment of the catalyst such as heating under hydrogen or in air at high temperatures or the electrochemical activation of the electrodes can also improve the performance for oxygen reduction [48,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65].…”
Section: Oxygen Reduction [39]mentioning
confidence: 99%
“…Pre-treatment of the catalyst such as heating under hydrogen or in air at high temperatures or the electrochemical activation of the electrodes can also improve the performance for oxygen reduction [48,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65].…”
Section: Oxygen Reduction [39]mentioning
confidence: 99%
“…A series of reaction pathways have been suggested for the methanol oxidation reaction and the subsequent CO oxidation, as given in Equations (18) to (21).…”
Section: Methanol Oxidationmentioning
confidence: 99%
“…Several works reported that Pt reached a maximum mass specific activity at a mean particle size of 3-5 nm [15][16][17][18], while others observed a straight increase of mass specific activity as Pt particle size decreased [19][20][21]. Peuckert et al [15], for instance, found that the ORR surface specific activity was constant with Pt particle sizes above 4 nm but it dropped by a factor of 20 when the particle size decreased from 3 nm to 1 nm, suggesting around 4 nm be the optimum Pt particle size for the maximum ORR mass specific activity. By depositing Pt on high surface area carbons, Watanabe et al [19], however, demonstrated a constant ORR surface specific activity when Pt particle size deceased to even 1.4 nm, indicating there was no Pt particle size effect on catalyzing the ORR.…”
Section: Introductionmentioning
confidence: 99%